Continuous sedation vs. daily sedation interruption in mechanically-ventilated children - Henri Azis; Silvia Triratna; Erial Bahar (Indonesian Pediatric Society, 2016)
Background A daily sedation interruption (DSI) protocol in ventilated patientsis an effective method of improving sedation management that decreases the duration of mechanical ventilation. In adult patients, it is a safe and effective approach, as well as common practice. For ventilated children,its effectiveness and feasibilityare unknown.Objective To compare continuous sedation and DSI in mechanically-ventilated children with respect todurationof mechanical ventilation, the time needed for patients to awaken, and the frequency of adverse events.Method This randomized, controlled, open-label trial, was performed in a pediatric intensive care unit (PICU). Forty children on mechanical ventilation were included. Patients were randomly assigned to receive either continuous sedation or DSI. The duration of mechanical ventilation was the primary outcome, while the time for patients to awaken on sedative infusion and the frequency of adverse events were secondary outcomes.Results Forty patients were randomized into the continuous sedation protocol (18 subjects) or into the DSI protocol (22 subjects). The median (interquartile range) duration of mechanical ventilation was significantly shorter in the DSI compared to the continuous sedation group [41.50 (30-96) hours vs. 61 (30-132) hours, respectively; (P=0.033)]. The time for patients to awaken was also significantly lower in the DSI than in the continuous sedation group [median (interquartile range): 28 (24-78) vs. 45.5 (25-12) hours, respectively; (P=0.003)]. The frequencies of adverse events were similar in both groups. The severity of illness contributed to outcome variables.Conclusion The duration of mechanical ventilation and the time for patients to awaken are significantly reduced in the DSI group compared to the continuous sedation group.